A randomized-controlled examination of the effect of cognitive reappraisal instruction on maternal accommodation of child anxiety symptoms. (August 2020) - O'Connor, Erin E.; Langer, David A.; Comer, Jonathan S.; Tompson, Martha C.
Highlights: The majority of studies examining factors related to parental accommodation of child anxiety symptoms are correlational. The present study sought to experimentally reduce accommodation by targeting parent attitudes about child anxiety. Brief instruction in reappraisal resulted in reduced maternal accommodation and distress in the context of child distress. Abstract: Parental accommodation plays a key role in the maintenance of child anxiety, yet much of the research to date has been correlational, making it difficult to draw conclusions about underlying mechanisms. Given preliminary evidence that parental beliefs play a role in parental accommodation, the present study sought to experimentally reduce accommodation by targeting parental attitudes about child anxiety. Mothers of children ages 4–9 (N = 47) were randomly assigned to either receive brief instruction in cognitive reappraisal (EXP) or to a control intervention in which they received no instruction (CON). At pre- and post-intervention mothers were presented with bogus information that their child was experiencing varying levels of distress while completing a task in a nearby room. Maternal distress, negative affect and perceived likelihood of accommodation in the context of child distress were measured pre- and post-intervention. EXP mothers reported greater pre- to post-intervention decreases in distress and perceived likelihood of accommodation, compared to CON mothers. EXP and CON mothers showed similar changes in negative affect. Findings from this study provide preliminary experimental evidence that targeting maternal beliefs about child anxiety can result in changes in maternal distress and behavior following exposure to child distress. Implications for prevention and treatment are discussed.